Identifying potential factors of adolescent online victimization in high school seniors - Marcum, Cathy (2008)
The purpose of this study was to investigate previous Internet usage in a sample of college freshmen, and to reflect on their experiences with online victimization, through variables representing the three constructs of Routine Activities Theory. A survey was administered to 100-level courses at a midsized university in the Northeast, which questioned respondents on their Internet behaviors and experiences with victimization during the high school senior period. The findings of the study indicated that participating in behaviors that increased exposure to motivated offenders and target suitability in turn increased the likelihood of the three types of victimization measured. Conversely, taking protective measures against victimization to improve capable guardianship generally did not decrease the likelihood of victimization. This research provides a significant contribution to the literature as there are few explanatory studies that attempt to identify reasoning for the victimization of adolescents online